ANALISIS PETROFISIKA UNTUK KARAKTERISASI RESERVOAR DAN PENGHITUNGAN CADANGAN HIDROKARBON DI LAPANGAN GRAHA, CEKUNGAN SUMATERA SELATAN - , NAVALDI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research on reservoir characterization to determine reservoir physics properties, area of hydrocarbon prospect zone, and calculate reserved original oil in place (OOIP) has been done on GRAHA field, in South Sumatera Basin. Petrophysics data analysis is used to determine shale volume, porosity, water saturation and netpay thickness. Seismic data analysis provides the area of hydrocarbon prospect zone. The result of petrophysiscs and seismic data analysis is used to estimate reserved original oil in place (OOIP) of the research area. Petrophysics analysis showed average thickness of hydrocarbon prospect zone is 14.92m, with 8.96 % average shale volume, 19.72% average effective porosity, and 47% average water saturation. Seismic data analysis showed that the area of hydrocarbon prospect zone is 9.95 km2. Total reserved original oil in place on GRAHA field is 16.98 million barrels.